Facebook, Quality of Life, and Mental Health Outcomes in Post-Disaster Urban Environments: The L’Aquila Earthquake Experience - Masedu, Francesco; Mazza, Monica; Di Giovanni, Chiara; Calvarese, Anna; Tiberti, Sergio; Sconci, Vittorio; Valenti, Marco (Frontiers in Public Health, 2014)
Background An understudied area of interest in post-disaster public health is individuals’ use of social networks as a potential determinant of quality of life (QOL) and mental health outcomes. A population-based cross-sectional study was carried out to examine whether continual use of online social networking (Facebook) in an adult population following a massive earthquake was correlated with prevalence of depression and PTSD and QOL outcomes. Methods Participants were a sample of 890 adults aged 25 to 54 who had been exposed to the L'Aquila earthquake of 2009. Definition of "user" required a daily connection to the Facebook online social network for more than one hour per day from at least two years. Depression and PTSD were assessed using the Screening Questionnaire for Disaster Mental Health (SQD). QOL outcomes were measured using the WHOQOL-BREF instrument. Logistic regression was carried out to calculate the prevalence odds ratios (POR) for social network use and other covariates. Results Two hundred and twenty one of 423 (52.2%) men, and 195 of 383 (50.9%) women, had been using Facebook as social network for at least two years prior to our assessment. Social network use correlated with both depression and PTSD, after adjusting for gender. A halved risk of depression was found in users vs. non-users (POR 0.50±0.16). Similarly, a halved risk of PTSD in users vs. non-users (POR 0.47±0.14) was found. Both men and women using online social networks had significantly higher QOL scores in the psychological and social domains of the WHOQOL-BREF. Conclusions Social network use among adults 25 to 54 years old has a positive impact on mental health and QOL outcomes in the years following a disaster. The use of social networks may be an important tool for coping with the mental health outcomes of disruptive natural disasters, helping to maintain, if not improve, QOL in terms of social relationships and psychological distress.